Legal Protection for Crime Victims in the Criminal Justice System - Winata, Rr. Ayu Azizah (Civiliza Publishing, 2025)
Crime victims in the criminal justice system often face situations where their rights are inadequately protected, both procedurally and substantively. This article aims to analyze the legal protection mechanisms for crime victims in Indonesia, covering applicable regulations, judicial practices, and implementation challenges. The method used is normative juridical research through a literature study of legislation, legal doctrines, and previous research findings. The analysis shows that although Indonesia has established a legal framework such as the Law on Witness and Victim Protection (Law No. 13 of 2006 jo. Law No. 31 of 2014), the Criminal Procedure Code (KUHAP), and other sectoral regulations, the realization of victim protection remains suboptimal. Victims often lack access to compensation, protection from intimidation, and psychological recovery services. Therefore, institutional strengthening, improved regulatory implementation, and the adoption of restorative justice approaches are needed to ensure more effective and equitable protection for victims.